A Systematic Literature Review of Influential Theories in Publicity Materials Development for English for Professional Communication - Novawan, Adriadi; Rukiati, Enik; Septian Indrastana, Nodistya; Arief Wicaksono, Julien; Tornado Taufan, Gullit; Ikeda, Osamu (Journal of English in Academic and Professional Communication, 2024)
Publicity materials are crucial tools in public relations, media communication, and marketing, playing a significant role in shaping public perception and disseminating key messages. This paper addresses the gap in comprehensive understanding and systematic exploration of the theoretical foundations and practical frameworks that guide the development of these materials. Utilizing a systematic literature review, we analyze existing frameworks and theories related to publicity materials, with a specific focus on their application in educational settings for undergraduate students learning English for Professional Communication. By synthesizing insights from seminal works and contemporary studies, this paper equips educators, students, and practitioners with a robust understanding of the principles, best practices, and innovative approaches for creating impactful publicity materials. Our findings highlight the evolution of publicity materials, the integration of digital platforms, personalization strategies, data analytics, and ethical considerations. These insights offer practical guidance for enhancing educational and professional development curricula, ensuring the effective use of publicity materials in various contexts.